Primary acquired hypothyroidism with associated myopathy in a 12-year-old female: the hidden face of hypothyroidism - Patel, Bhargav G. (International Journal of Contemporary Pediatrics, 2025)
Primary acquired hypothyroidism with autoimmune aetiology can present with atypical neuromuscular features in pediatric patients. We reported a case of a 12-year-old female presenting with calf muscle pain, pseudohypertrophy, decreased physical activity, and rapid weight gain. Laboratory investigations revealed markedly elevated thyroid stimulating hormone, low free T4, and significantly raised anti-thyroglobulin antibodies. Early diagnosis and prompt initiation of levothyroxine led to dramatic clinical and biochemical improvement. This case highlights the importance of considering thyroid dysfunction in the differential diagnosis of pediatric myopathies.